A study on the crack presence effect on dynamical behavior of higher-order Quasi-3D composite steel-polymer concrete box section beams via DQFEM - Nassim Laouche; Ahmed Saimi; Ismail Bensaid; Mouloud Dahmane; Hassen Ait Atmane (Fracture and Structural Integrity, 2025)
This paper presents a dynamic and critical buckling analysis of the presence of a crack of steel-polymer concrete composite beams modelled using a refined quasi 3D beam theory. The beam model is a hollow steel box section filled with a composite concrete material. The presence of the crack is assumed on both inner concrete core and outer steel layer box, incorporating its effects into the mechanical behavior of the beam. The governing equations for the box beam are derived using the Differential Quadrature Finite Element Method (DQFEM) combined with Lagrange’s principle. The study investigates the natural frequencies and critical buckling loads of steel-polymer concrete composite beams under various crack location and crack depth. Validation is performed by comparing the results with numerical methods and experimental results available in the literature, demonstrating high accuracy. The findings of this research provide valuable insights into the dynamic and stability behavior of box-section beam with composite infill, offering practical guidelines for the design of material-based structures in engineering applications.